Exploring repellency of odors from non-host plants native to Xinjiang, China to Aphis gossypii - Bian, Zhipeng; Zhang, Ying; Liu, Bing; Zhang, Tao; Yuan, Haibin; Lu, Yanhui (Frontiers in Plant Science, 2025)
IntroductionThe cotton aphid (Aphis gossypii Glover) is a major global agricultural pest that damages cotton and numerous other economically significant crops through feeding and virus transmission. It possesses high adaptability and rapid reproduction rates, contributing to widespread resistance to chemical insecticides and thereby reducing the effectiveness of such control methods. It should be noted that plants have developed advanced chemical defense mechanisms over long periods of synergistic evolution, allowing them to synthesize volatile compounds. These compounds not only defend against herbivorous insects but also crucially reduce the development of pest resistance. Consequently, this study strives to explore plant-emitted volatiles as a potential eco-friendly alternative for aphid management.MethodsIn this study, we first tested the behavioral responses of A. gossypii to the volatile blends of fifteen native plant species in Xinjiang, China, using a Y-tube olfactometer and cage experiments. We identified six out of fifteen plant species that were repellent to A. gossypii. We then collected the volatile compounds of repellent plants using a headspace collection method and used gas chromatography-mass spectrometry (GC-MS) to identify the key components. The antennal responses of winged A. gossypii to the compounds were evaluated with an antennal potential test. Finally, further testing using a Y-tube olfactometer and Petri dish experiments.ResultsWe identified six out of fifteen plant species (i.e. Anethum graveolens L., Juglans regia L., Rhaponticum repens L., Karelinia caspia Pall., Launaea polydichotoma Ostenf., and Brassica rapa L.) that were repellent to A. gossypii. We collected the volatile compounds of these six repellent plants and identified thirty-one key components. Our electroantennogram (EAG) tests revealed that sixteen of the thirty-one compounds caused significant antennal responses in winged A. gossypii. Further testing using a Y-tube olfactometer and Petri dish experiments confirmed fourteen compounds that repelled intact, winged cotton aphids.DiscussionOur study report that the volatiles of four plant species – R. repens, K.caspia, L. polydichotoma, and B. rapa – present a significant repellent effect on winged cotton aphids, suggesting that these compounds might be useful for eco-friendly cotton aphid pest management. These results provide essential theoretical foundations and practical knowledge for the application of plantderived repellent volatiles.